Culture, development and social theory : towards an integrated social development - Clammer, J. R. (Zed Books, 2012)
"Culture, Development and Social Theory places culture back at the centre of debates in development studies. It introduces new ways of conceptualizing culture in relation to development by linking development studies to cultural studies, studies of social movements, religion and the notion of ?social suffering?. The author expertly argues that in the current world crises it is necessary to recover a more holistic vision of development that creates a vocabulary linking more technical (and predominantly economic) aspects of development with more humanistic and ecological goals. Any conception of post-capitalist society, he argues, requires cultural, as well as economic and political, dimensions."-- Publisher's website